Hallucinations and related concepts—their conceptual background - Telles-Correia, Diogo; Moreira, Ana Lúcia; Gonçalves, João S. (Frontiers in Psychology, 2015)
Prior to the 17th century, the experiences we now name hallucinations or others alike were valued within a cultural context, they could bring meaning to the subject or the world. From mid-17th to 18th centuries, they acquire a medical quality in mental and organic illnesses. However, the term was only fully integrated in psychiatry by Esquirol in the 18th-19th centuries. By then, a controversy begins on whether hallucinations have a perceptual or intellectual origin. Esquirol favours the intellectual origin, describing them as an involuntary exercise of memory and imagination. By the twentieth century, some authors maintain that hallucinations are a form of delusion (Ey), while others describe them as a change in perception (Jaspers, Fish). A more integrated perspectives like those proposed by Alonso Fernandez and Luque, highlights the heterogeneity of hallucinations and the multiplicity of their types and causes. The terms pseudohallucination, illusion and hallucinosis are grafted into the concept of hallucination. Since its introduction the term pseudohallucination has been used with different meanings. The major characteristics that we found associated with pseudohallucinations were ‘lack of objectivity’ and ‘presence of insight’ (differing from hallucinations). Illusions are unanimously taken as distortions of real objects. Hallucinosis, first described in the context of alcohol consumption, is generally considered egodystonic, in which insight is preserved. These and other controversial aspects regarding the evolution of the term hallucination and all its derivative concepts are discussed in this paper.